Temperature-Controlled Continuous Cold Flow Device after Total Knee Arthroplasty: A Randomized Controlled Trial Study - Ruffilli, Alberto; Castagnini, Francesco; Traina, Francesco; Corneti, Isabella; Fenga, Domenico; Giannini, Sandro; Faldini, Cesare (The Journal of Knee Surgery, 2017)
Total knee arthroplasty (TKA) is a widely accepted and successful procedure for end-stage arthritis. Nevertheless, fast-track may be compromised by many factors, such as pain, edema, and blood loss. Cryotherapy has been advocated as a safe and effective strategy to improve the postoperative results, acting on pain, edema, and blood loss. This study is a prospective randomized controlled study, involving 50 patients after primary TKA. A power analysis was performed preoperatively. Twenty-four patients were addressed to a postoperative treatment with a continuous cold flow device (Hilotherm, Hilotherm GmbH, Germany). Twenty-six patients represented the control group, treated with crushed ice packs. All the patients shared the same analgesic strategy and the same rehabilitation protocol. Pain, analgesic consumption, active knee range of motion, drain output, transfusion requirement, and total blood loss were evaluated at different follow-ups (postoperative first, third, and seventh days). The two groups were homogenous for preoperative and intraoperative features. The groups showed no statistically significant differences in all the evaluated parameters. A modest reduction of knee volume was evident after 7 days from surgery (trend). No differences in blood loss were noticed. Continuous cold flow device in the acute postoperative setting after TKA did not show superiority in reducing edema, pain, and blood loss, compared with traditional icing regimen. Thus, due to the costs, it should be reserved to selected cases.
Keywords: continuous cold flow device; cryotherapy; total knee replacement; total knee arthroplasty; randomized controlled trial